Research on Characteristics of the Piloted Follow-up Load Control Valve in Automobile Crane Luffing System - Haibo Xie; Guolong Zhang (2013 Fifth International Conference on Measuring Technology and Mechatronics Automation, 2013)
Automobile crane luffing system is a variable load system. While the boom is being lowered, the constantly changing geometry results in a steadily increasing load pressure acting on the luffing cylinder. This requests the load control valve to have perfect performance including opening characteristic, jiggle characteristic, load pressure over-compensation characteristic and dynamic response characteristic. However the luffing hydraulic system with traditional load control valve has the problems of high system pressure, large impact and easily vibrated. This paper introduces the working principle of a new piloted follow-up load control valve first, and then develops a simulation model, which is validated by a series of experiments conducted on the automobile crane. Based on theory research and simulation, the working mechanism is analyzed and it demonstrates that the piloted follow-up load control valve have a opening characteristic independent of load, good jiggle characteristic under low control pressure, load pressure over-compensation, and smooth dynamic response without overshoot, which are all essential in automobile crane luffing system.